Pengawasan Tempat Pemeriksaan Keamanan Pertama Terhadap Implementasi Keamanan Penerbangan - Dian Artanti Arubusman; Ollipin Jusnibilna; Agus Setiawan (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of the research is to find out the effect of the first security inspection place monitoring to flight safety implementation in Husein Sastranegara International Airport. The analysis techniques used in this study were simple linier regression, coefficient correlation, determinant coefficient and hypothesis test. The result shows that there is a balance effect between the first security inspection place monitoring and flight safety implementation based on simple linear regression analysis Y = 20,601 + 0,656X which means each changes from one variable X will be followed by Y changes of 0,656 times X in constant of 20,601. Based on coefficient correlation analysis, r= 0.735 is close to 1 that there is a strong and positive relation between the first security inspection place monitoring and flight safety implementation in Husein Sastranegara International Airport. Based on the determinant coefficient analysis, 54 % shows the contribution of variable X (first security inspection place) to variable Y (flight safety implementation) while the other 42 % is from other factors. The last result is t count > t table: 5,729 > 1,701 from hypothesis test which means there is a significant relation between X and Y variables (Ho is rejected while Ha is accepted).